Sodium Sulfide: A Sustainable Solution for Unbalanced Redox Condensation Reaction between o-Nitroanilines and Alcohols Catalyzed by an Iron–Sulfur System - Nguyen, Thanh Binh; Ermolenko, Ludmila; Al-Mourabit, Ali (Synthesis, 2015)
Unbalanced redox condensation reaction between o-nitroanilines and alcohols, leading to benzimidazole and quinoxaline heterocycles can be efficiently promoted and catalyzed by sodium sulfide (40 mol%) in combination with iron(III) chloride hexahydrate (1 mol%). Beside the role as a precursor for the iron–sulfur (Fe/S) catalyst formation, hydrated sodium sulfide was shown to be an excellent noncompetitive, multi-electron reducing agent.
Keywords: redox condensation; iron–sulfur; benzimidazole; atom economy; sodium sulfide